Quantity judgments in bilingual speakers (Yudja/Brazilian Portuguese) - Lima, Suzi Oliveira de (Letras de Hoje, 2015)
This paper contributes to investigations on language-specific encoding of the count mass distinction. Two quantity judgment studies tested adult bilingual speakers in two languages that encode the count-mass distinction differently: Yudja and Brazilian Portuguese. In Yudja all nouns have count denotations. That is, all nouns (including notional mass nouns like ‘water’) can be directly combined with numerals and with count quantifiers. Conversely, in Brazilian Portuguese count and mass nouns are grammaticalized in different ways. For example, only count nouns can be directly combined with numerals. In two studies with 20 Yudja bilingual adults we investigate whether the performance of Yudja speakers in quantity judgment tasks varied depending on the language that they were operating. ************************************************************************************************************************************************************************************************************ Julgamentos de quantidade em falantes bilíngues (Yudja/Português Brasileiro) Este artigo contribui para o debate sobre a codificação gramatical da distinção contável-massivo. Dois julgamentos de quantidade testaram adultos bilíngues em duas línguas que codificam a distinção contável-massivo de formas diferentes: Yudja e o português brasileiro. Em Yudja todos os nomes têm uma denotação contável. Isto é, todos os nomes (incluindo nomes nocionalmente massivos como água) podem ser diretamente combinados a numerais e a quantificadores contáveis. Por outro lado, no português brasileiro, nomes contáveis e massivos são gramaticalmente distintos. Por exemplo, somente nomes contáveis podem ser diretamente combinados a numerais. Em dois estudos experimentais com 20 falantes bilíngues da língua Yudja, nós investigamos se a performance dos falantes Yudja bilíngues em tarefas de julgamento de quantidade variavam de acordo com a língua na qual eles eram testados. Palavras-chave: Contável-massivo; Semântica; Aquisição; Bilinguismo; Tarefa de julgamento de quantidade